Effects of Probiotic, Prebiotic, and Synbiotic Mixed Culture Based on Wheat Pollard on Productivity of Kampung’s Chicken - Cahya Setya Utama; Zuprizal Zuprizal; Chusnul Hanim; Wihandoyo Wihandoyo (Jurnal Ilmu Ternak dan Veteriner, 2020)
This research was aimed to assess the effectiveness of processed wheat pollard -based rations to increase the productivity of Kampung chickens raised until 8 weeks old. The research was carried out in a completely randomized design with 5 treatments and 4 replications. The treatments consisted of wheat pollard based ration (WP), wheat pollard based ration plus probiotic mixed culture (WPPro), wheat Pollard as prebiotic mixed (WPPre)            , wheat pollard as synbiotic mixed culture ration 40% (WPS40), wheat pollard as synbiotic mixed culture ration 60% (WPS60)   . The parameters observed were feed consumption, final body weight, feed conversion ratio (FCR), weight gain, nitrogen retention, income over feed and chick cost (IOFCC) and profiles of intestinal villus. Results showed a significant effect of the treatments on the final body weight, weight gain, nitrogen retention, IOFCC and profiles of small intestinal villus (duodenum, jejenum, ileum). It was concluded that the inclusion of 40% wheat pollard synbiotic mixed culture (WPS 40) in the ration was able to increase the productivity of kampung chickens reared until 8 weeks old.